Chemical composition and antimicrobial effect of Melissa officinalis and Angelica sylvestris on selected microbial pathogens - RASHA HADI SALEH; ASEEL MOHAMMAD OMRAN; HALA SAAD BASH (Society for Indonesian Biodiversity, 2023)
Abstract. Saleh RH, Omran AM, Bash HS. 2023. Chemical composition and antimicrobial effect of Melissa officinalis and Angelica sylvestris on selected microbial pathogens. Biodiversitas 24: 1871-1877. Melissa officinalis L. and Angelica sylvestris L. have been used for traditional herbal medicines due to their antimicrobial action against pathogenic microbes. The purpose of this research was to determine the chemical content of the aqueous and ethanol extracts of M. officinalis and A. sylvestris and their antimicrobial activity against selected bacteria and fungi. This study was done from March 2022 to July 2022. The antimicrobial activity of the extracts was carried out against three bacterial isolates (Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae) and one fungal isolate (Candida albicans). The fungal isolate was isolated from the different patients. The concentrations of extracts were 10, 20, 30, 40 mg/mL. The antimicrobial activity was performed using agar diffusion methods and compared to standard gentamycin and fluconazole disc. It has been shown that the major phytochemical composition in M. officinalis and A. sylvestris aqueous and ethanolic extracts were: alkaloids, phenols, glycosides, and flavonoids. The extracts of M. officinalis and A. sylvestris exhibit different antimicrobial activity against the tested microorganisms, and their activity increased with increasing extract concentration. Melissa officinalis extracts inhibited the growth of all tested microorganisms except C. albicans. Aqueous and ethanol extracts of M. officinalis were more effective against E. coli. A. sylvestris aqueous extract was the most effective against S. aureus. The most potent antimicrobial activity of the ethanolic extract was detected against K. pneumoniae. The antimicrobial properties of M. officinalis and A. sylvestris are related to their chemical compounds, such as phenols, alkaloids, glycosides, and flavonoids. Both plants extract showed good inhibition against most microorganisms. Based on the research results, M. officinalis and A. sylvestris are potential new sources of antimicrobial agents.